(untitled) (Nigerian Journal of Technology, 2013)
Unfettered effluent discharge, in addition to seasonal runoffs, into Ikpoba River, have been blamed for the ever poor water quality noticed in the river. This study seeks to investigate the role of industrialization and/ or urbanization on the degraded water quality of the river. Chemical analyses of samples of the river water collected at predetermined sampling points were undertaken and the observations obtained were subjected to ANOVA, correlation, and eigenvalue analysis. Results obtained showed that each point source has its relative contribution to the overall degradation of the river water quality. In merit order, the eigenvalue analyses carried out suggests that phosphate, nitrate, cadmium, copper, iron, lead and turbidity are the most offensive factors showing values of 0.868, 0.933, 0.770, 0.503, 5.063, 0.717, 30mg/L respectively. Remarkably, surface runoffs from municipal drains channelled to stations 1 and 2 contribute significantly to the turbidity with 4.333 and 4.233mg/L respectively, whereupon urbanization and industrialization are seemingly the culprits.